Analisis Kontribubsi Budaya Organisasi dan Kompetensi terhadap Kinerja Karyawan Universitas Muhammadiyah Lamongan - Nisa Widya Zulistian; Almas Nurul Jannah (Yayasan Aya Sophia Indonesia, 2026)
Increasing workforce productivity in an institution is highly dependent on the effectiveness of human resource (HR) management. A key strategy believed to be able to improve workforce capabilities is through the establishment of a strong work culture and the development of personal competencies, so that all team members can contribute optimally and align with the organization's vision. However, in its implementation, organizations often face challenges in achieving performance targets, in the form of heterogeneity in mindsets, background experiences, and levels of capabilities between individuals. This study uses an associative quantitative methodology with the primary objective of examining how organizational culture (X1) and competency (X2) influence employee performance (Y) at Muhammadiyah University of Lamongan. The findings of this study indicate that both variables, when tested together, have a significant and positive contribution to employee work performance. However, when analyzed separately, only the competency variable shows a significant influence on improving individual performance at Muhammadiyah University of Lamongan.